Study of Identity Politics in the 2019 Simultaneous Regional Head Election in Tarakan City, Indonesia - Arri Bima Prastya; Umar Nain (Borong Newinera Publisher, 2023)
As an archipelagic country with the largest number of ethnic groups and religions in the world, Indonesia is a multicultural and multi-religious country which currently influences the democratic process in Indonesia, one of which is the Regional Head Election (Pilkada). Tarakan City is an ethnically and religiously diverse city which in its democratic process is still influenced by issues of religious and ethnic sentiment which are accommodated and used well by political elites as instruments in every regional head election. This research uses a qualitative approach with case studies. Data collection techniques use interviews, documentation and audio visuals. The theories used in this research are identity politics, multiculturalism, political participation, political elites, and simultaneous regional elections. The data analysis used in this research refers to a data analysis model which includes three stages, namely data reduction, data presentation, and data verification. Based on the research results, it shows that political elites and regional head candidates seem to deliberately maintain or play identity politics, for political interests and power hegemony. This had an impact on the political reality in the 2019 Simultaneous Regional Head Election in Tarakan City. With a certain identity, regional head candidates can hold a bargaining position, which shows that ethnic and religious factors are significant enough to gain support and influence people's choices in the 2019 Simultaneous Regional Elections in Tarakan City. This also proves that the people of Tarakan are voters who only care about figures and similar backgrounds rather than the skills and abilities of regional head candidate pairs.